Study of intellectual capital on drugs and pharmaceutical industry of India: Using panel data analysis - S. Singhal; S. Gupta; V. K. Gupta (Финансы: теория и практика, 2022)
Intellectual capital is becoming increasingly important in financial decisions made by managers in the information-based environment. However, only a small portion of a company’s total assets is represented by intangible assets (such as concessions, licenses, patents, and trademarks). The current research investigates the relationship between an organization’s Intellectual capital and its health. A new model — Modified Extended Value-added Intellectual Capital Coefficient — was also proposed. The findings were compared with the two existing models, namely, Value Added Intellectual Coefficient and Modified Value Added Intellectual Coefficient. Panel data regression is used to assess the performance of 25 Indian pharmaceutical and drug companies throughout the period 2010–2019. Human capital efficiency, structural capital efficiency, and relational capital efficiency have been proven to have a substantial positive correlation with return on assets (ROA). In addition, a negative yet significant link exists between organizational capital efficiency and a company’s profitability. Under the Value Added Intellectual Coefficient, human capital and structural capital efficiency do not affect the market value to book value. The market value-to-book value, on the other hand, is positively impacted by capital employed efficiency.